Current State and Future Trends of Research on Pressure Injuries in Nursing Homes: Network Analysis and Topic Modeling - Chang, Sung Ok; Lee, Ye-Na (Journal of Wound Management and Research, 2025)
Background: Pressure injuries (PIs) are a significant issue in nursing homes (NHs) that affect residents’ physical, psychological, and financial well-being. Despite advancements in prevention and management, PIs remain a critical challenge requiring a comprehensive analysis of research trends to guide future efforts.Methods: We analyzed 1,857 research abstracts published up to December 2023 using text network analysis and topic modeling. Keyword frequency, co-occurrence patterns, and centrality metrics were examined to identify the key terms. Latent Dirichlet allocation was employed for topic modeling, and trends were analyzed over decades to explore the evolution of research priorities.Results: The most frequent keywords were “patient,” “care,” and “wound,” emphasizing the central themes of patient care and wound management. Four main topics were identified: Managing PI Complications, Preventing PIs and Maintaining Skin Integrity, Improving Organizational Strategies for PI Care, and Managing Systemic Conditions in PI Care. Trends revealed a decline in studies on post-injury management, while prevention and organizational strategies have gained prominence. Patient-specific risk factors have consistently attracted attention over the decades, highlighting the importance of individualized care.Conclusion: This study underscores the shift from reactive post-injury management to proactive prevention and organizational strategies in PI research. These findings emphasize the need for integrated approaches that combine patient-centered care with systemic and preventive measures to improve outcomes in NHs.